2017
DOI: 10.1186/s12884-017-1465-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal delivery: how does early hospital discharge affect mother and child outcomes? A systematic literature review

Abstract: BackgroundThere is an international trend to shorten the postpartum length of stay in hospitals, driven by cost containment, hospital bed availability and a movement toward the ‘demedicalization’ of birth. The aim of this systematic literature review is to determine how early postnatal discharge policies from hospitals could affect health outcomes after vaginal delivery for healthy mothers and term newborns.MethodsA search for systematic reviews, meta-analyses, and primary studies was carried out in OVID MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 39 publications
7
52
0
2
Order By: Relevance
“…Evans et al (2018) investigated the impact of early discharge on outcomes among infants and found no differences in the outcomes of early and late discharge. However, the authors conducted a meta-analysis on the same data and found no study that reported any differences, even though there was an international trend toward shortening the postpartum length of stay in hospitals among women who have undergone vaginal delivery to improve the mother's sleep, for proper bonding of the mother and infant, and to protect the infant-mother dyad from nosocomial infections (33). Our analysis showed a 1.95-fold increase in the frequency of maternal hospital admissions among exposed subjects compared to non-exposed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al (2018) investigated the impact of early discharge on outcomes among infants and found no differences in the outcomes of early and late discharge. However, the authors conducted a meta-analysis on the same data and found no study that reported any differences, even though there was an international trend toward shortening the postpartum length of stay in hospitals among women who have undergone vaginal delivery to improve the mother's sleep, for proper bonding of the mother and infant, and to protect the infant-mother dyad from nosocomial infections (33). Our analysis showed a 1.95-fold increase in the frequency of maternal hospital admissions among exposed subjects compared to non-exposed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ED of mothers and newborn has in fact increased dramatically in several high-income countries over the past 10-15 years. However, the evidence on the impact of ED on healthy mothers and term newborns (≥37 weeks) after a vaginal delivery (VD) is still inconclusive and little is known of the characteristics of those discharged early [5][6][7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…Although RCTs are more appealing than others, a very narrow focus either to a hospital or a small community (Boulvain et al ., ; Brooten et al ., ) has made them unconvincing to generalize their results to a large population. Furthermore, it was not always possible to choose early and late discharge women (treatment and control groups) randomly, as women with delivery complications tend to stay longer and vice versa (Benahmed et al ., ). Most of the studies, including the two studies for developing countries, belong to NRCTs, which have estimated correlations or associations, as their treatment and control groups were not comparable in most of the cases.…”
Section: Empirical Evidencementioning
confidence: 97%
“…As the previous studies have produced highly mixed results, recent systematic reviews have found inconclusive findings (Benahmed et al ., ; Jones et al ., ). Indeed, there is a lack of proper causal studies.…”
Section: Empirical Evidencementioning
confidence: 99%